2013
DOI: 10.5770/cgj.16.79
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in Delirium: a Retrospective Cross-sectional Study

Abstract: BackgroundAs vitamin D may have a neuroprotective effect, the authors studied the association of biomarkers of vitamin D status and delirium to see if low vitamin D status was common in delirium cases.MethodsBiochemical measures of vitamin D (25-hydroxyvitamin D [25-OHD]) and calcium metabolism were used in this retrospective cross-sectional analysis of adult in-patients with delirium, admitted at three Canadian academic hospitals from January 2011 to July 2012. Primary outcome was to determine estimates of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Vitamin D receptors has been located in the human cortex and hippocampus, which are key areas for cognition and may regulate neurotransmission, neuroprotection and neuro immuno modulation including anti-inflammatory and antioxidant effects (90)(91)(92). This may explain our findings for vitamin D. A cross sectional study examined 25(OH)D in patients who experienced a delirium found a common hypovitaminosis D in delirious patients (150), and a pilot study of intensive care unit patients showed that low vitamin D was associated with delirium at borderline significance (148). However, Lapid et al studied hypovitaminosis D in a geriatric psychiatric ward and found no association between vitamin D and cognitive function including delirium, however only n= 13 patients with delirium were presented in this study (151).…”
Section: Is Specific Micronutrient Deficiency Related To Increased Rimentioning
confidence: 76%
“…Vitamin D receptors has been located in the human cortex and hippocampus, which are key areas for cognition and may regulate neurotransmission, neuroprotection and neuro immuno modulation including anti-inflammatory and antioxidant effects (90)(91)(92). This may explain our findings for vitamin D. A cross sectional study examined 25(OH)D in patients who experienced a delirium found a common hypovitaminosis D in delirious patients (150), and a pilot study of intensive care unit patients showed that low vitamin D was associated with delirium at borderline significance (148). However, Lapid et al studied hypovitaminosis D in a geriatric psychiatric ward and found no association between vitamin D and cognitive function including delirium, however only n= 13 patients with delirium were presented in this study (151).…”
Section: Is Specific Micronutrient Deficiency Related To Increased Rimentioning
confidence: 76%
“…Because of a possible correlation between preoperative vitamin D levels and the occurrence of POD, serum-levels of 25-hydroxy vitamin D (25-OHD) will be checked for all patients preoperatively [ 45 , 46 ]. Furthermore, different blood samples will be collected at baseline (visit 0), at 1 hour after end of surgery (visit 2) and postoperative day 1 (visit 3).…”
Section: Methodsmentioning
confidence: 99%
“…Our results are in accordance with the scarce previous literature. Ford et al found hypovitaminosis D (ie, insufficiency <75 nmol/L or deficiency <25 nmol/L) in 66% of people diagnosed with delirium from three Canadian university hospitals (12). Similarly, in a cohort of more than 4,000 patients, Quraishi et al reported that serum 25OHD concentration <25 nmol/L prior to hospitalization was associated with an increased risk of delirium during the hospital stay (16), which suggested that the vitamin D status could be a changeable risk factor for delirium acquired during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is an acute neurocognitive disorder leading to greater morbidity (pressure ulcers, infectious diseases, fall risk, disability), complicated care course (prolonged hospital stays, more frequent readmissions, increased healthcare costs), and greater mid-term mortality ( 10 12 ). Pathophysiology of delirium remains not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%